Yevgeniy Daniilovich Goldberg - article Editorial (Бюллетень сибирской медицины)
Here it has been presented the creative biography of the greatest person in Russian medical science — RF honored scientist, member of Russian Academy of Medical Sciences (RAMS), Honorary professor of Siberian State Medical University, Director of Pharmacology research institute of RAMS SB TSC, Yevgeniy Daniilovich Goldberg.